Yoga for enhancing emotional intelligence - Archana Kumari; Kamta Prasad Sahu (Wolters Kluwer Medknow Publications, 2018)
Emotional intelligence (EI) plays a very important role in life satisfaction, the quality of interpersonal relationships, academic success, and success in occupations that involve considerable reasoning with emotional information. Emotional sensitivity, emotional maturity, and emotional competency are the three important psychological dimensions of EI, which motivate student to recognize truthfully, interpret honestly, and handle tactfully the dynamics of their behavioral pattern. Yoga has been reported to improve emotional regulation and mental health. This brief review will discuss about the significance of EI for students and the possibility of implementing yoga as an intervention to improve EI.